Adaptive release of heparin from anticoagulant hydrogels triggered by different blood coagulation factors. (August 2017) - Maitz, Manfred F.; Zitzmann, Jan; Hanke, Jasmin; Renneberg, Claudia; Tsurkan, Mikhail V.; Sperling, Claudia; Freudenberg, Uwe; Werner, Carsten
Abstract: Feedback-controlled anticoagulant hydrogels were formed by crosslinking the anticoagulant heparin with star-shaped poly(ethylene glycol) using peptide linkers, which are selectively cleaved by different activated blood coagulation factors acting as proteolytic enzymes. Various cleavable peptide units, differing either in their thrombin turnover rates or in their responsiveness to factors activated earlier in the course of blood coagulation, were used for the formation of the biohybrid materials. Release triggered by the early coagulation factors Xa (FXa) or FXIIa/kallikrein was shown to enhance the efficiency of the released anticoagulant. Furthermore, FXa-cleavable gels enabled a faster release of heparin, which was attributed to the lower affinity of the factor for heparin. Combining early and fast responses, FXa-cleavable gels were shown to provide anticoagulant protection of biomaterial surfaces at low levels of released heparin in human whole-blood incubation experiments. The results demonstrate the potential for employing biomolecular circuits in the design of functional biomaterials to tailor the adaptive delivery of bioactive molecules.